'You're basically calling doctors torturers': stakeholder framing issues around naming intersex rights claims as human rights abuses. Issue 4 (5th March 2020) - Crocetti, Daniela; Arfini, Elisa A. G.; Monro, Surya; Yeadon‐Lee, Tray
Abstract: In this article we address activist, patient advocate and medic perspectives on framing intersex, variations of sex characteristics and disorders/differences in sex development medical treatment as human rights abuses. Problematic aspects of intersex medical treatment have increasingly been highlighted in national debates and international human rights bodies. Some intersex activists have framed aspects of intersex medical treatment as human rights abuses since the 1990s. Other stakeholders in shaping medical treatment, such as patient advocates and medical professionals, are not always content with human rights framing, or even the term intersex. In order to address the different perspectives in this arena we provide background on the primary rights claims that have arisen followed by key human rights framing of these claims. We provide a short discussion of activism styles, looking at pan‐intersex social movements and variation‐specific patient associations as different styles of health social movements. The analysis of stakeholder perspectives on the use of human rights strategy in health areas provides a useful case study for medical sociology and policy in general.